Land Surface Evaluation Using Unit Hydrograph Methods at Way Besai Watershed, Sumberjaya, West Lampung, Indonesia - Manik, Tumiar Katarina (UNIVERSITY OF LAMPUNG, 2011)
Sumber Jaya is an important water resource area for Lampung Province; therefore the local government protects this area, especially from clearing the forest for coffee plantation. However, the efforts in protecting the forest area had created conflict with the local farmers. The objective of this research was to evaluate catchments hydrological function from different land cover condition. The method using for this purpose was by investigating the unit hydrograph of each land cover which were observed from several rain events. The results showed that soil cover on each sub-catchment were relatively able to hold the input water. When rain falls, water was infiltrated into the soil before flow to the streams and water level increased slowly. When rain stops, water still flowed from the soil surface that water level did not decrease quickly. It can be concluded that the watershed surface was still in a good condition; however, watershed managements to prevent it from future destruction was necessary. The rest of forest area (12%) should be protected and no further coffee plantation in this area was allowed.Keywords: Unit hydrograph, water level, watershed